The Theological Support of the Concept of Justice in Plato’s Laws - Terezis, Christos Ath.; Stavropoulou, Olga Chr. (Études helléniques / Hellenic Studies, 2004)
In this paper, the authors study one specific aspect of Plato's Philosophy of Justice in The Laws. According to the authors, Plato proceeds to a particularly systematic view of Justice in this Dialogue and, since The Laws is probably the latest of Plato's Works, this view constitutes "the most significant objective criterion" for the philosopher's theses on Justice. The authors examine, specifically, Plato's attempts (Bk X) to associate Justice with his theological theses.